Organizational commitment: A case study in the Specialized Care Center in the municipality of Malhada de Pedras-BA - Misquita , Amélia Guimarães; Silva, Camila Naiara Ferreira da; Souza, Débora Ribeiro Oliveira; Santos, Deykiane Nájila Brito dos; Brito, Iasmim de Sá Mendes; Ribeiro, Joelma de Oliveira Santos; Almeida , Jossiele Fernandes Lisboa; Silva, Juçara Aguiar Guimarães; Barreto, Núbia Pereira Macena; Rodrigues , Selma Cristina Pires; Martins , Thais Vieira da Silva; Brito, Noé de Souza (Seven Editora, 2024)
This article analyzes the organizational commitment of the specialized care center in the municipality of Malhada de Pedras-BA. The research data was collected using questionnaires and the measurement was made based on the authors who deal with the topic in question. . This research is characterized by a case study and data analysis was based on the LIKERT scale. The results of this research can serve as a parameter for the Institution’s Human Resources policy, demonstrating that there is a high level of commitment among its employees DOI:https://doi.org/10.56238/sevened2024.007-031